EDUKASI PORTABLE AND ECO-FRIENDLY OF GABION (POLYGON) KOMBINASI CANGKANG KERANG DAN BATU SEBAGAI PENGENDALI EROSI SUNGAI [PORTABLE AND ECO-FRIENDLY OF GABION (POLYGON) EDUCATION, THE COMBINATION OF SHELLFISH AND STONE FOR CONTROL RIVER EROSION] - Miguel Felix Wijaya; Niko Rizaldi; Maharani Miranda; Harpian Surya; Ramadhan Yanuari; Monita Olivia (Jurnal Sinergitas PKM & CSR, 2018)
Uncontrolled erosion will endanger the people on the banks of the river. One of the bad consequences is the land down and the landslides, as happened in the Lubuk Lande River, Teratak Buluh Village. This river is located on the edge of Lubuk Street, initially the Lubuk road has a width of 3.5 m, the road gradually narrows to 3 m wide. Therefore, Community Service (PKM) activities are needed, in order to develop knowledge, skills, optimize natural resources and waste by making portable and eco-friendly of Gabion (polygon). Polygon is an innovation of making gabion using waste shellfish, river stones and vetiver plants as a controller of river erosion. Polygon is designed with a beam shape with 3 frames, the first frame is filled with river stone material, the second frame is filled with a mixture of stone and shells, and the third frame is filled with shellfishs and vetiver plants. polygon is placed on the side of the river which often experiences erosion, namely the river turn area. This PKM activity was carried out for two days with the community and cadres. The first day was an educational activity, while the second day was the implementation of polygon. The results of this activity indicate an increase in community knowledge and contributions about controlling river erosion.